Morphological and nutritional diversity among accessions of marvel grass (Dichanthium annulatum (Forssk.) Stapf) and development of a core collection. (2nd November 2021) - Roy, A. K.; Malaviya, D. R.; Kaushal, P.; Mahanta, S. K.; Tewari, R.; Chauhan, R.; Chandra, A.
Abstract: Dichanthium annulatum is one of the dominant grasses of India, North Africa, Southeast Asia, China, Australia, Fiji, New Guinea, Cuba, Haiti and Puerto Rico. This drought-tolerant grass is an excellent fodder in mixed pastures. Developing varieties with improved quality and tolerance to various abiotic stresses is hampered due to its apomictic nature. Germplasm collection, characterization, genetic diversity analysis and core subset development followed by selection for desirable traits seems to be the most plausible breeding tool for developing new cultivars. In the present study, 498 genotypes collected from different agro-ecological zones in India were included. Genotypes were characterized for various metric and non-numeric traits; and the nutritional parameters. Agglomerative clustering analysis, using the Euclidean distance method, showed 14 distinct clusters. High variability was recorded for green forage yield, quantitative traits and nutritive quality parameters. A core subset of 50 accessions was identified, which captured most of the morphological and nutritional variability present in the total germplasm. Clustering of genotypes was observed to be related to the climatic conditions of the place of collection. High genetic variability observed for various morphological traits as well as forage yield indicated that these genotypes or subset of genotypes can be evaluated in different abiotic stress conditions such as salt, light and moisture stress for the identification of suitable varieties for the respective areas. Variability was attributed to inter-generic, inter-specific crossing together with the occasional presence of sexual plants in nature.